HUBUNGAN DUKUNGAN SOSIAL DENGAN SELF COMPASSION PADA MAHASISWA DI MASA PANDEMI COVID-19 - Muhammad Zein Azra (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2022)
The COVID-19 pandemic has brought changes in the learning system to online. Changes in the learning system have an impact on the number of problems that arise in students so that self-compassion is needed to overcome these problems. Social support is predicted to help students to have self-compassion. This study aims to determine the relationship between social support and self-compassion for students in the COVID-19 pandemic. The sample in this study amounted to 270 students (male 19.3% and female 80.7%) Faculty of Psychology UIN Suska Riau with a sampling technique using stratified random sampling. Data collection methods in this study used a social support scale (Sarafino, 1998) and a self-compassion scale (Neff, 2003). Based on the results of the product moment correlation analysis obtained a correlation value of 0.462 with a significance of 0.000. The results showed that the hypothesis was accepted, which means that there is a relationship between social support and self-compassion for students during the COVID-19 pandemic.